School Belonging and the Mental Health of Adolescents: A Scoping Review - Speranza, Marina (2025)
Introduction. The sense of belonging has been considered a fundamental factor for the understanding of the mental health of adolescents, especially when it comes to the school context. Objective. To analyze the scientific literature on the theme of the sense of belonging to the school context in adolescence and its relationship with the mental health of this population. Method. A scoping review was conducted, guided by the Joanna Briggs Institute (JBI) and the PRISMA checklist, with searches in the Web of Science, Scopus, SciELO, and the Virtual Health Library databases, using terms in English, Portuguese, and Spanish. Studies that addressed school belonging among adolescents and its relationship with mental health were selected. Results. The studies found are recent, in their majority quantitative, and are concentrated in developed countries. There is a gap in the production of knowledge on the subject in a participatory way, especially in the African continent and in South America, where no studies have been identified, except one in Chile. In the thematic analysis, categories of analysis were listed that deal with the sense of belonging as a protective factor for mental health in adolescents, interventions that seek to increase the school belonging of teens, and the perspective of teens on what favors and what prevents belonging to the school. Conclusions. There is a need for more productions on the theme of the sense of belonging in adolescence and its relationship with the mental health of this population, especially based on participatory methodologies.